Whole-plant silage maize to improve fiber digestive characteristics and intestinal microbiota of Hezuo pigs - Wang, Longlong; Wang, Pengfei; Yan, Zunqiang; Zhang, Pengxia; Yin, Xitong; Jia, Rui; Li, Yao; Yang, Jiaojiao; Gun, Shuangbao; Yang, Qiaoli (Frontiers in Microbiology, 2024)
Utilizing roughage resources is an effective approach to alleviate the shortage of corn-soybean feed and reducing the costs in the swine industry. Hezuo pig is one group of plateau type local Tibetan pig with strong tolerance to crude feeding. Nevertheless, current research on the roughage tolerance in Hezuo pigs and the microbiological mechanisms behind it is still minimally.This study explored the impact of various ratios of whole-plant silage (WPS) maize on the pH, cellulase activity, short-chain fatty acids (SCFAs), and intestinal microbiota in Hezuo pigs. Thirty-two Hezuo pigs were randomly divided into four groups (n=8). The control group received a basal diet, while experimental groups I, II, and III were given diets with incremental additions of 5%, 10%, and 15% air-dried WPS maize, respectively, for 120 days. The findings revealed that compared with the control group, in Group II, the pH of cecum and colon were notably decreased (P<0.05), while acid detergent fiberdigestibility, the concentration of propionic and isobutyric acid in the cecum, and the concentration of isobutyric acid in the colon were significantly increased (P<0.05). Also, carboxymethyl cellulase activity in the cecum in group II of Hezuo pigs was significantly higher than that in the other three groups (P<0.05). Furthermore, the cecum microbiota showed a higher diversity in the group II of Hezuo pigs than that in the control group, as shown by the Simpson and Shannon indices. Specifically, 15 and 24 bacterial species showed a significant difference in relative abundance at the family and genus levels, respectively. Correlation analyses revealed significant associations between bacterial genera and SCFAs concentrations in the cecum. The abundance of Bacteroides and NK4A214_group was positively correlated with amounts of valeric and isovaleric acid but negatively with propionic acid (P<0.05). The abundance of UCG-010 was positively linked with acetic acid and negatively correlated with butyric acid (P<0.05). Actinobacillus abundance was positively associated with butyric acid levels (P<0.05). In conclusion, a 10% WPS maize diet improved crude fiber digestibility by lowering cecal and colonic chyme pH, enhancing intestinal cellulase activity, improving SCFA production, and increasing intestinal microbiota diversity.